TINDAK TUTUR ILOKUSI DALAM FILM “KU KIRA KAU RUMAH” - Aryani Dwi Inggria Putri; Yuni Kusumawati; Zulma Amalia Firdaus; Hera Septriana; Asep Purwo Yudi Utomo (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
Language is a communication tool used by humans to convey intentions, thoughts, ideas, feelings to others. The purpose of this study is to identify and describe the types of ilocutionary speech acts in the film “Ku Kira Kau Rumah”. This research is inclueded in qualitative descriptive research. The origin of the data in this study is in the form of speech fragments that are suspected to contain ilocutionary speech acts in the film “Ku Kira Kau Rumah. The data of this research is in form of speech fragments that are suspected to contain illocutionary speech acts in the film “Ku Kira Kau Rumah”. The data collection technique in this study was a free listening technique, involving conversation and taking notes. The data sourch used is the film “Ku Kira Kau Rumah” using a study of the division of Searle’s speech acts including representative, directive, expressive, commissive, and deklarative. According to the result of the analysis of the film “Ku Kira Kau Rumah” found 5 types of illocutionnary speech acts, namely representative consisting of 3 data, namely the act of stating, showing, and informing. The directive consist of 2 data, namely the act of ordering and asking. Expressive consist of data, namely acts of gratitude and apologizing. Commissive which consist of 1 data, namely acts of promise, and Declarative consisting of 1 data, namely acts of decision.